Effect of the precursor nature and preparation mode on the coarsening of La2Zr2O7 compounds. Issue 1 (January 2016) - Duarte, William; Vardelle, Michel; Rossignol, Sylvie
Abstract: This study addresses the thermal behavior of La2 Zr2 O7 powders prepared via two different synthetic routes and the effect of the zirconium counter-cation on their properties, as carried out by dilatometric experiments. Citrate-based compounds exhibit shrinkage, regardless of the precursors used. Preliminary thermal treatment permits the reduction in shrinkage. Nitrate based compounds calcinated at 600 °C show a higher shrinkage (−9.4%) than at 1200 °C (−5.2%) because of the decomposition of the trapped precursors, as revealed by DTA–TGA–MS. Coprecipitated samples present different behaviors as a function of the counter-cation nature. Chloride based compounds leads to shrinkage and phase mixtures, whereas expansion is observed for pure pyrochlore compounds that are synthesized with nitrate. The thermal expansion coefficients of the different compounds are similar to the literature values (9.5–10.10 −6  K −1 ). This study allowed for a better understanding of the densification of the La2 Zr2 O7 material and its adjusted properties, as a function of the precursor nature and the preparation mode, for application in thermal barrier coatings.